Blood pressure reduction following bilateral adrenal demedullation of young spontaneously hypertensive rats; comparison between normal saline and distilled water supplementation postoperatively - Mohd Noor, Noriah; Abdullah, Aszrin; Abdul Razak, Tariq (2011)
Normal saline (0.9% NaCl) supplementation is recommended to replace sodium loss in adrenal demedullation postoperatively . We propose that normal saline supplementation is not required postoperatively following adrenal demedullation. Twenty four young male and female SHRs weighing 200-270g and 150-170g, respectively were studied. Six were sham-operated age-matched controls (Group 1) were given distilled, 10 adrenal demedullated SHRs were given 0.9% NaCl supplementation (Group 2) and 8 adrenal demedullated SHRs were given distilled water (Group 3). Indirect systolic blood pressures (SBPs) was measured by tail cuff method preoperatively,1 week and 2 weeks postoperatively. The mean preoperative SBP in Groups 1, 2 and 3 were 168.78 + 5.80, 164.05 + 17.11 and 163.15 + 16.26 mmHg respectively. The mean postoperative SBP at 1 week were 170.00 + 9.61, 132.79 + 19.91 and 128.31 + 19.36 mmHg respectively (p values of 0.753, 0.005 and 0.012, Wilcoxon Signed Ranks Test - compaired to preoperative mean values). The mean postoperative SBP at 2 weeks were 167.08 + 6.87, 138.50 + 17.73 and 129.00 + 13.34 mmHg respectively (p values of 0.753, 0.005 and 0.028, Wilcoxon Signed Ranks Test). There was no significant difference in the mean values between Groups 2 and 3 at 1 week and 2 weeks postoperatively (p values of 0.423 and 0.278, Mann-Whitney U). Adrenal demedullation results in chronic SBP reduction in SHRs given normal saline or distilled water postoperatively. Therefore, ad libitum normal saline supplementation is not essential in postoperative, adrenal demedullated SHRs as there is minimal adrenal cortical damage during demedullation